Atmospheric electrical field decrease during the M = 4.1 Sousel earthquake (Portugal) - Silva, H. G. (2012)
This paper presents a work that aims to monitor seismo-electromagnetic phenomena in the Western Part of the Eurasia-Nubia Plate Boundary. This region has a significant tectonic activity combined with relatively low electromagnetic noise levels, rendering high quality seismoelectromagnetic measurements possible. An overview of the seismicity of this region is presented and the research plan is discussed accordingly.